Der demografische Wandel in Europa und die Folgen für Familien - Wittrahm, Andreas (European Journal of Mental Health, 2015)
The Demographic Transformation of Europe and Its Impact on Families: Population structure is in transition throughout the European Union. With life expectancy rising and birth rates dropping in most countries, societies are increasingly ageing. As a result, the face of society is also changing: it is becoming progressively older. In addition to demographic changes, cultural changes can also be observed: not only is family size declining, but families are also started later, and motherhood and fatherhood are often detached from the formal establishment of a family. Family policy and social policy must take these changes into account in order to support families in practising mutual care and in their central functions as economic, educational and emotional communities.